FRONTLINER SERVICES IN PT KAI COMMUTER JABODETABEK NEW KLENDER STATION, EAST JAKARTA - Setyo Rini, Ratih; Wijayanti, Mei (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
Service excellent will produce satisfaction for customers. Many companis now are providing the best service to get consumers satisfaction. This research is to find out the implementation of service excellent provided by the frontliner officer PT KAI Commuter Jabodetabek at Klender Baru Station in East Jakarta. The research conducted through qualitative method from January to February 2017. Frontliner officer who became the main service at PT KCJ in Klender Baru Station is divided into several parts including: Officer Counters, Announcer, Passager Service and Inside Security Officer (PKD). The results show that PT KCJ has a good service procedure, and also shown through the report that PT KJC has less complaint from the passenger. Nevertheless, service excellent implementation is still facing the obstacles, such as train travel disturbance, queue at the counter, and lack of seats to wait for the train. Suggestions for PT KCJ to add train travel and additional facilities such as seats and gate-in gate-out Machines